2018
DOI: 10.1208/s12249-018-1190-1
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of an Oral Vaccine Formulation Using Electrosprayed Chitosan Microparticles

Abstract: Chitosan particles loaded with the antigen ovalbumin (OVA) and the adjuvant, Quil-A were produced by electrospray, using mixtures of water/ethanol/acetic acid as a solvent. Three different chitosan's designed as HMC + 70, HMC + 85 and HMC + 90 (designated as 705010, 855010 and 905010) were tested and its efficacy to be used in oral vaccine delivery applications was investigated. The morphology, size and zeta potential of the produced particles were investigated, together with the encapsulation efficiency and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
(64 reference statements)
1
1
0
Order By: Relevance
“…For this purpose, the use of chitosan as one of the most effective polymers for improving the transmucosal absorption of molecules (the ability to open intercellular tight junctions), its mucoadhesive property, and permeability enhancement were shown in this study and in others [39][40][41][42][43]. Similar studies with other delivery systems with chitosan composition also showed a controlled release of protein/peptide [40,43].…”
Section: Discussionsupporting
confidence: 78%
“…For this purpose, the use of chitosan as one of the most effective polymers for improving the transmucosal absorption of molecules (the ability to open intercellular tight junctions), its mucoadhesive property, and permeability enhancement were shown in this study and in others [39][40][41][42][43]. Similar studies with other delivery systems with chitosan composition also showed a controlled release of protein/peptide [40,43].…”
Section: Discussionsupporting
confidence: 78%
“…Vaccine-loaded microgels fabricated from a synthetic polymer were shown to be taken up by M-cells and simulate an immune response [154]. Various other kinds of CDSs have also been investigated for their potential of enhancing the efficacy of orally-administered vaccines, including starch microparticles [160], chitosan microparticles [161], hydrophobic polymer particles [162], phospholipid liposomes [157,163], W/O/W emulsions [164,165], and polymer nanoparticles [166].…”
Section: Vaccinesmentioning
confidence: 99%